Black and blue : the bruising passion of Camera lucida, la Jetée, Sans soleil, and Hiroshima mon amour - Mavor, Carol, 1957- (Duke University Press, 2012)
Postwar French works that register disturbing truths about loss and regret, and violence and history, through aesthetic refinement anchor this exquisite, image-filled rumination on efforts to capture fleeting moments and comprehend the incomprehensible.